(untitled) (Nuntius Antiquus, 2012)
Abstract: This paper presents as interpretation of the short-story “Famigerado” by João Guimarães Rosa (Primeiras estórias) and the Polyphemus’ episode in Homer’s Odyssey based on many common elements: the smart use of language; an adjective related to fame that occupies a central place in the story (“famigerado”; “polyphêmos”); a hospitality scene structuring the story; and the dialectic movement between violence and cunning.